The Effectiveness of Group Guidance Using Problem Solving Technique to Prevent Learning Saturation of Grade 8B Students in SMP Negeri 4 Yogyakarta - Adi Ramdani Putra Dinanti; Aprilia Setyowati; Fadhila Malasari Ardini (Journal of Education and Counseling (JECO), 2023)
In this study, the objectives achieved by researchers reached the stage of knowing how effective the provision of group guidance services is problem solving techniques to reduce learning saturation. This type of research is quantitative with a pre-experimental method with a one group pretest-posttest design. The population taken in this study was class 8B students, then the research sample was 6 students. This research instrument uses a learning saturation scale that has been tested for validity and reliability. In addition to the scale, decision making in this study used the normality test and SPSS 26-assisted T test. Based on the results of the study, 6 students had medium and high categories with details of 2 students having high scores and 4 having moderate scores. After being given the service, the 6 students experienced a decrease in score. This can be shown by the pretest score which totaled 344 with a mean of 57.3 then after being given group guidance services the problem-solving technique decreased with a total score of 231 with a mean of 38.5. In addition, based on the results of the sample t test, it is known that the sig. (2 tailed) is 0.001 meaning that 0.001 is less than <0.05, then Ha is accepted, and Ho is rejected. So, it can be concluded that group guidance services with problem solving techniques are effective in preventing student learning saturation.